(untitled) (Global Journal of Human-Social Science, 2015)
Recent trends have shown that cities of developing countries have been switching from one urban planning approach to another and this trend will continue The methodology adopted involved a review of scondary data sources interviews and analysis The findings of this research present three areas of discourse First the demise and resurgence of conventional approaches is a worldwide recurring phenomena Secondly the switch return to master planning approach in Dar es Salaam was premature and largely resulted from a misconception of the theory of paradigm shift Thirdly the claim that SUDP is ill-suited to guide the process of urban change is more of a misleading generalization than a reality The utility of SUDP has to be examined not only from practice but also from core theoretical and conceptual tenets laws and procedures governing such an urban planning practice